Life cycle of chicken bursal secretory dendritic cell (BSDC) - Imre Oláh; Balázs Felföldi; Zsófia Benyeda; Attila Magyar; Nándor Nagy; Ádám Soós; Emőke Szőcs (Poultry Science, 2024)
ABSTRACT: The transmission electron microscopy revealed a dendritic cell in the medulla of the chicken bursal follicle. This dendritic cell has a classical secretory machinery; therefore, it has been named a bursal secretory dendritic cell (BSDC). The corticomedullary epithelial arch (CMEA) encloses lymphoid-like cells, which can proliferate and after entering the medulla, begin to differentiate to immature, then mature BSDC, which discharges glycoprotein (gp). With the exhaustion of gp production, the BSDC rapidly transforms into a macrophage-like cell (Mal), which is an activated endocytic cell of innate immunity. The Mal drifts through the follicle-associated epithelium (FAE)-supporting cells into the FAE, and via FAE, the Mal is eliminated in the bursal lumen. The infectious bursal disease virus (IBDV) infection accelerates the maturation process of BSDC precursors, which results in acute emptying of CMEA and subsequently, numerous immature BSDC(s) emerge. The IBDV infection stops the gp discharge, and the gp appears in the virus-containing Mal. The Movat pentachrome staining recognizes the gp in the extracellular spaces of the medulla and after infection in the Mal. The BSDC is the primary target of the IBDV. During IBDV infection, a large number of suddenly formed Mal actively migrate into the cortex, initiating cytokine storm and recruiting heterophil granulocytes. During embryogenesis, the vimentin-positive, possibly embryonic dendritic cells provide a microenvironment for carbohydrate switch. Around hatching, these embryonic, temporary dendritic cells get the Fc receptor, which bind maternal IgY. The posthatched forms of BSDC(s) gradually replace the embryonic ones and bind their own IgY.